Multiple Wives, Co-wives and Female Status: Example on Contemporary Change from Manipur (India) - ManiBabu, Mayanglambam (Researcher: A Research Journal of Culture and Society, 2013)
DOI: http://dx.doi.org/10.3126/researcher.v1i1.8372 Researcher: A Research Journal of Culture and Society Vol.1(1) 2013